THE IMPORTANCE OF REGULARLY ORGANIZING TRAINING FOR THE CURRENT MEDICAL EQUIPMENT MANAGEMENT TO ENSURE THAT MEDICAL AND TECHNICAL EMPLOYEES CAN CONSCIOUSLY CARRY OUT THE MAINTENANCE OF MEDICAL EQUIPMENT (World Bulletin of Public Health, 2024)
In the past decades in Uzbekistan international financial institutions are providing direct support for the reform of the country's medicine, particularly for the creation of new medical facilities and the provision of state-of-the-art medical equipment and high-tech facilities. This makes it possible to increase the coverage of qualified medical services provided to the population. In particular, in 2023 advanced medical equipment worth 150 million US dollars was planned to be procured and delivered to medical establishments. Of the allocated funds, 124.5 million US dollars are foreign soft loans, and 25.5 million US dollars are foreign direct investments. The Government also plans to strengthen cooperation with a number of countries and international organizations, such as KfW, KOICA, JICA, USAID, to attract $100 million in grant funds (www.ssv.uz ).
Keywords: Experience shows; procurement process; regulatory standards